Competitive Exclusion vs. Mimetic Isomorphism? An Identified Empirical Test - William Barnett; Xiao Xiao; Yi Zhou (Sociological Science, 2021)
Why are organizations sometimes so similar, and in other cases so different? For decades this question has been central to research on organizations, and two leading theories have answered the question very differently. Neo-institutional theory has pointed to the importance of mimetic isomorphism, where organizations imitate one another as they navigate decisions in the context of uncertainty over what is regarded as legitimate action. By contrast, ecological theory argues that competitive exclusion explains the differences we see around us, as organizations repel one another when they vie for the same resources. Decades of empirical work has tended to confirm one or the other theory, with scant effort being made to reconcile these conflicting predictions. Furthermore, much of the existing empirical work is limited to descriptive studies that make little or no attempt to empirically identify their findings, leaving the empirical record open to concerns over endogeneity. This paper conducts an identified empirical test, in a context where the two arguments make opposing predictions. In an analysis of auditor selection after the collapse of Arthur Andersen, we find evidence of competitive exclusion, but no evidence of mimetic isomorphism. Implications for the continued progress of organization theory are discussed.